2010
DOI: 10.1007/s11307-010-0308-y
|View full text |Cite
|
Sign up to set email alerts
|

[(Methyl)1-11C]-Acetate Metabolism in Hepatocellular Carcinoma

Abstract: Purpose Studies have established the value of [(methyl)1-11C]-acetate ([11C]Act) combined with 2-deoxy-2[18F]fluoro-d-glucose (FDG) for detecting hepatocellular carcinoma (HCC) using positron emission tomography (PET). In this study, the metabolic fate of [11C]Act in HCC was characterized. Methods Experiments with acetic acid [1-14C] sodium salt ([14C]Act) were carried out on WCH-17 cells and freshly derived rat hepatocytes. PET scans with [11C]Act were also carried out on woodchucks with HCC before injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…In the woodchuck HCC animal model 11 C-Act uptake is associated with de-novo tumoral lipogenesis [23] and fatty acid synthase activity. Phosphatidylcholine and triacylglycerol are the main metabolites into which the radioactive label from 11 C-Act accumulates in HCC.…”
Section: C-act Petmentioning
confidence: 99%
“…In the woodchuck HCC animal model 11 C-Act uptake is associated with de-novo tumoral lipogenesis [23] and fatty acid synthase activity. Phosphatidylcholine and triacylglycerol are the main metabolites into which the radioactive label from 11 C-Act accumulates in HCC.…”
Section: C-act Petmentioning
confidence: 99%
“…This and other observations support speculation that imaging of choline metabolism can be used to monitor tumor lipogenesis[12,18]. The reason why choline-based tracers may be needed to assess tumor lipogenic activity despite 11C-acetate being available is that acetyl-CoA formed from acetate can also serve as a metabolic substrate for a variety of metabolic processes, including oxidative metabolism, histone modification, and cholesterol biosynthesis[19].…”
Section: Do We Need To Further Validate Imaging Biomarkers Of Lipogenmentioning
confidence: 56%
“…Upregulated FAS expression is a frequently observed phenomenon in many tumor types[4]. However, while the constitutive role of FAS in liver and adipose tissue is to create stored energy in the form of triglycerides, the primary role for FAS in cancer cells appears to be to supply fatty acids for phospholipid membrane synthesis[11,12]. Glycolysis, which is also frequently upregulated in cancer[1], can not only fuel this process by providing ATP, but also contribute substrate for de-novo lipogenesis by producing acetyl-CoA.…”
Section: Metabolic Pathways Combine To Support Membrane Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Increased rates of de-novo fatty acid synthesis have been observed in many cancers (28), and pre-clinical experiments using radiolabeled acetate have shown that a significant proportion of de-novo fatty acids are incorporated by PtC in HCC (29). Indeed, [ 11 C]-acetate has been proposed as a PET tracer for detecting HCC on the basis of imaging de-novo fatty acid synthesis, with clinical studies supporting its potential diagnostic efficacy (30).…”
Section: Discussionmentioning
confidence: 99%